Robust Adaptive Synchronization of Dynamic Networks With Varying Time Delay Coupling Using Variable Structure Control - Ojleska, Vesna M.; Tükel, Dilek (Bilgin); Dimirovski, Georgi M. (ASME, 2014)
The synchronization problem for a class of delayed complex dynamical networks via employing variable structure control has been explored and a solution proposed. The synchronization controller guarantees the state of the dynamical network is globally asymptotically synchronized to arbitrary state. The switching surface has been designed via the left eigenvector function of the system, and assures the synchronization sliding mode possesses stability. The hitting condition and the adaptive law for estimating the unknown network parameters have been used for designing the controller hence the network state hits the switching manifold in finite time. Two illustrative examples along with the respective simulation results are given, which employ the designed variable structure controllers.